Evaluation of the Use of Different Sensitive Cardiac Biomarkers in Determining Myocardial Damage in Cows With Subclinical and Clinical Ketoses - Murat Uztimür; Cennet Nur Ünal; Meltem Sağiroğlu (Veterinary Medicine and Science)
ABSTRACT Background It is unclear whether the increase in BHBA concentration damages the myocardium in ketotic cows. Measurement of troponin is the gold standard in myocardial injury. Objective The objective of this study was to explore the impact of elevated β‐hydroxybutyrate (BHBA) concentrations on myocardial damage in cows diagnosed with subclinical ketosis (SCK) and clinical ketosis (CK). Additionally, the study aimed to elucidate the relationship between heart‐type fatty acid–binding protein 3 (H‐FABP 3) and high‐sensitivity cardiac troponin I (hs‐cTnI) concentrations, as well as their correlation with various biochemical parameters that assess myocardial and metabolic health. Methods The animal material used in this study consisted of 30 postpartum Holstein cows, aged between 2 and 5 years. The study group comprised 10 cows with SCK, 10 with CK and 10 cows in the control group (CG). Results The concentration of hs‐cTnI in cows with CK was significantly higher compared to both the CG (p < 0.005) and the SCK group (p < 0.019). Similarly, the H‐FABP 3 concentration in the CK and SCK groups was significantly elevated compared to the CG (p < 0.001). The creatinine kinase myocardial band (CK‐MB) levels were significantly higher in cows with CK compared to the CG (p < 0.010). Furthermore, the aspartate aminotransferase (AST) levels in the CK group were significantly elevated compared to the CG (p < 0.011). A significant positive correlation was observed between BHBA concentration and the levels of both hs‐cTnI and H‐FABP 3 in ketotic cows. Additionally, significant correlations were found between various biochemical parameters (alanine aminotransferase [ALT], AST, CK‐MB and phosphorus) and the concentrations of H‐FABP 3 and hs‐cTnI. Conclusions This study showed that high BHBA concentrations in ketosis cows may indirectly cause myocardial damage. However, future studies need to investigate the relationship between oxidative stress and changes in antioxidant concentrations and troponin.